Meta-Analysis: The Use of Mindfulness-Based Cognitive Therapy for Depression Symptoms - Arisudana, Made; Yudiarso, Ananta (Kuras Institute, 2024)
This meta-analysis investigates the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) in addressing depression across diverse contexts. Drawing from 13 studies, it examines the impact of MBCT on depressive symptoms using various measurement tools such as the Depression Anxiety and Stress Scale (DASS) and Beck-Depression Inventory (BDI). The findings underscore the importance of tailoring intervention materials to participant characteristics and completing the full MBCT program for significant outcomes. Additionally, components of MBCT, such as mindful awareness and cognitive restructuring, emerge as key factors in reducing depressive symptoms. Moderator analysis reveals no significant difference between in-person and internet-based MBCT delivery, highlighting the importance of consistent participation and mindfulness practice for successful outcomes.